2014
DOI: 10.1128/jvi.03472-13
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Transmitted/Founder and Chronic Clade B HIV-1 Vpu and a C-Terminal Polymorphism Specifically Affecting Virion Release

Abstract: Acute HIV-1 infection is characterized by a type I interferon response, resulting in the induction of host restriction factors. HIV-1 has evolved to counteract these factors, and one such adaptation, the ability of Vpu to counteract BST2/tetherin, is associated with the evolution of simian immunodeficiency virus (SIV cpz ) into pandemic group M human immunodeficiency virus type 1 (HIV-1). During transmission between individuals, very few viruses or even a single virus, the "transmitted/founder" (T/F) virus, gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 46 publications
3
35
0
Order By: Relevance
“…HIV-1 counteracts tetherin using its Vpu protein, which binds tetherin and prevents its expression on the cell surface (62)(63)(64). However, TF Vpu proteins do not seem to counteract tetherin more effectively than the Vpu protein of chronic viruses (65). Moreover, TF-infected CD4 + T cells were shown to produce more cell-free virions even in the absence of Vpu (54).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 counteracts tetherin using its Vpu protein, which binds tetherin and prevents its expression on the cell surface (62)(63)(64). However, TF Vpu proteins do not seem to counteract tetherin more effectively than the Vpu protein of chronic viruses (65). Moreover, TF-infected CD4 + T cells were shown to produce more cell-free virions even in the absence of Vpu (54).…”
Section: Discussionmentioning
confidence: 99%
“…The source of this residual activity has been attributed to the ability of Vpu to displace BST2 from virion-assembly sites in the plane of the membrane, an activity that has been roughly mapped to the C-terminal portion of the cytoplasmic domain of Vpu (16). During an analysis of naturally occurring Vpu proteins, we found the converse phenotype: the preserved ability to degrade and down-regulate BST2 yet impaired enhancement of virion release (17). This phenotype mapped to a W76G polymorphism, a mutation that presumably arises in infected hosts to provide escape from cytotoxic T lymphocytes.…”
mentioning
confidence: 93%
“…This phenotype mapped to a W76G polymorphism, a mutation that presumably arises in infected hosts to provide escape from cytotoxic T lymphocytes. Site-directed mutagenesis confirmed that optimal enhancement of virion release depends upon Trp-76, which is near the C terminus of Vpu and is well conserved in certain HIV-1 clades (17). Substitution of a glycine for Trp-76 impairs virion release without affecting the ability of Vpu to co-localize with BST2, to downregulate BST2 from the cell surface, or to reduce the steadystate amount of cellular BST2.…”
mentioning
confidence: 95%
See 2 more Smart Citations